PERAN ORANG TUA DALAM PEMBELAJARAN DARING DI MASA PANDEMI COVID 19 PADA KELOMPOK B.5 TK KEMALA BHAYANGKARI BONE - Nurhasanah, Nurhasanah (EDUCHILD (Journal of Early Childhood Education), 2020)
Online learning is an option that educational institutions must undertake in order to cut the spread of the covid-19 virus. No exception in Kemala Bhayangkari Kindergarten, Bone Regency, especially in group B5, where the implementation of learning uses the online method, where the process requires the role of parents in helping their children's learning. This study aimed to determine how the role of parents in online learning at TK Kemala Bhayangkari Bone. The method used is qualitative with a case study approach, through data collection by means of observation, interviews, and documentation. The results showed that online learning in group B5 TK Kemala Bhayangkari Bone was carried out by following the policies of the Minister of Education and Culture of the Republic of Indonesia Number 4 of 2020 concerning the provisions of the learning process from home. The role of parents in online learning at TK Kemala Bhayangkari Bone is in the form of 1) Assisting students in every online learning process, 2) Facilitating students in carrying out various activities, 3) Motivating students so that they continue to feel happy, happy, and complete activities - learning activities well.Keywords: Parents, Learning, Online